ASSOCIATION BETWEEN LEUKEMIC EVOLUTION AND UNCOMMON CHROMOSOMAL ALTERATIONS IN PEDIATRIC MYELODYSPLASTIC SYNDROME - Viviane Lamim Lovatel; Beatriz Ferreira da Silva; Eliane Ferreira Rodrigues; Maria Luiza Rocha da Rosa Borges; Rita de Cássia Barbosa Tavares; Ana Paula Silva Bueno; Elaine Sobral da Costa; Terezinha de Jesus Marques; Teresa de Souza Fernandez (Mediterranean Journal of Hematology and Infectious Diseases)
Background and objective: Pediatric myelodysplastic syndrome (pMDS) is a group of rare clonal neoplasms with a difficult diagnosis and risk of progression to acute myeloid leukemia (AML). The early stratification in risk groups is essential to choosing the treatment and indication for allogeneic hematopoietic stem cell transplantation (HSCT). According to the Revised International Prognostic Scoring System, cytogenetic analysis has demonstrated an essential role in diagnosis and prognosis. In pMDS, abnormal karyotypes are present in 30-50% of the cases.  Monosomy 7 is the most common chromosomal alteration associated with poor prognosis. However, the rarity of specific cytogenetic alterations makes its prognosis uncertain. Thus, this study aimed to describe uncommon cytogenetic alterations in a cohort of 200 pMDS patients and their association with evolution to AML. Methods: The cytogenetic analysis was performed in 200 pMDS patients by G-banding and fluorescence in situ hybridization between 2000 to 2022. Results: Rare chromosome alterations were observed in 7.5% (15/200) of the cases. These chromosome alterations were divided into four cytogenetic groups: hyperdiploidy, biclonal chromosomal alterations, translocations, and uncommon deletions, which represented 33.3%, 33.3%, 20%, and 13.3%, respectively. Most of these patients (10/15) were classified with advanced MDS (MDS-EB and MDS/AML) and the initial subtype was present in five patients (RCC). The leukemic evolution was observed in 66.66% (10/15) of the patients. Most patients had poor clinical outcomes and they were indicated for HSCT.  Conclusion: The study of uncommon cytogenetic alterations in pMDS is important to improve the prognosis and guide early indication of HSCT.